Enhancing proton conductivity in Zr-MOFs through tuning metal cluster connectivity. Issue 3 (22nd December 2021) - Si, Guang-Rui; Yang, Fan; He, Tao; Kong, Xiang-Jing; Wu, Wei; Li, Tong-Chuan; Wang, Kecheng; Li, Jian-Rong
Abstract : Improving proton conductivity in Zr-MOFs through enhancing metal cluster connectivity. Abstract : We design and synthesize two stable Zr(iv )-based metal–organic frameworks with high proton conductivity, namely BUT-76 and BUT-77, which are constructed with the same sulfonic acid containing ligand and 8/12 connected Zr6 clusters. The proton conductivity of these two materials at 80 °C and 100% relative humidity (RH) can reach 8.55 × 10 −3 and 3.08 × 10 −2 S cm −1 correspondingly. Moreover, both BUT-76 and BUT-77 can maintain their high conductivity and framework integrity for at least 120 hours under the test conditions. XRD diffraction measurements and comprehensive molecular simulations are conducted to explore how the increased connectivity of Zr6 clusters can significantly enhance the proton conductivity of the materials by changing the proton carrier concentration and hydrogen-bonding network. Furthermore, the BUT-77 mixed-matrix membrane shows a proton conductivity value of 1.25 × 10 −3 S cm −1 (80 °C, 100% RH). This work not only presents promising candidate materials for proton exchange membranes, but also demonstrates an example to use MOF as a platform to reveal the relationship between structural features and proton conductivity.